2016
DOI: 10.22146/ijg.12498
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Recreational Facilities in Federal Capital City, Abuja, Nigeria

Abstract: Abuja Master Plan provided development of adequate Green Areas and other Recreational Facilities within the Federal Capital City (FCC), as part of its sustainability principles and provided for these recreational facilities within each neighborhood (FCDA, 1979). However, there have been several recent foul cries about the negative development of recreational facilities and the abuse of the Master Plan in the FCC. The motivation for carrying out this study arose from the observation that recreational facilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They are also in line with view that having developments around the boundaries of greenbelts (where there exist) and relying on Brown fields as alternative sources of urban land for housing can help to conserve greenbelts in urban areas [15]. Notably, the idea of having physical developments beyond the boundaries of greenbelts can help in air pollution control and storm water runoff reduction, reduction in urban heat island [18,19], enhancement of the aesthetics value of urban landscape, [37,52], provision of place for relaxation [24,52], leisure and recreation activities within urban neighbourhoods [53]. Similarly, the suggestion on the use of Brownfields for housing development seems to have great potentials in the study area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are also in line with view that having developments around the boundaries of greenbelts (where there exist) and relying on Brown fields as alternative sources of urban land for housing can help to conserve greenbelts in urban areas [15]. Notably, the idea of having physical developments beyond the boundaries of greenbelts can help in air pollution control and storm water runoff reduction, reduction in urban heat island [18,19], enhancement of the aesthetics value of urban landscape, [37,52], provision of place for relaxation [24,52], leisure and recreation activities within urban neighbourhoods [53]. Similarly, the suggestion on the use of Brownfields for housing development seems to have great potentials in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…88 of 1992 has made provision for urban centers to have a good proportional of land use designated as open spaces from which recreation parks could be developed for leisure, physical exercises and in Environmental and Socio-Economic Development of Urban Areas in Southeast Nigeria social interactions, and for environmental sustainability. In line with this, it has been revealed that in Nigerian's Federal Capital Territory (FCT), Abuja, greenbelts in forms of parks and gardens such as Millennium Park, Abuja Zoological Park and Gardens, Orange Park and Gardens, National Children's Park and Zoo and others have been created for relaxation, recreation and improvement of the city's environmental sustainability status [53]. In Owerri, the existing greenbelts have also been identified as key sources of medicinal plants and food tree; and thus contributing to the health of the residents [25].…”
Section: Greenbelts and Urban Development Agendamentioning
confidence: 91%
See 1 more Smart Citation